Structural, Dielectric and Electrical Properties of Ba-modified PbWO4 Ceramics - Singh, N.K.; Mishra, Shikha (Asian Journal of Chemistry, 2016)
Polycrystalline samples of Ba-doped lead tungstate Pb1BaxWO4 (x = 0.0, 0.05, 0.10, 0.15) have been prepared by a high-temperature solid-state reaction technique. Preliminary X-ray diffraction studies of these compounds suggested the formation of a single-phase compound with the tetragonal crystal structure at room temperature. Detailed studies of dielectric constant (e) and tangent loss (tan d) as a function of frequency (400 Hz to 10 kHz) and temperature (room temperature to 598 K) suggest that the above compounds are non-ferroelectric/non-polar with low activation energy, but interestingly contain space-charge polarization at high temperature.